The prevalence of intellectual disability: A comparison of national census and register records. (June 2019) - McConkey, Roy; Craig, Sarah; Kelly, Caraíosa
Abstract: Background: International prevalence rates for intellectual disability vary widely with estimates often based on samples. In Ireland people with an intellectual disability are identified in the national census. Moreover, a national register of people receiving or requiring intellectual disability services is maintained and updated annually. Aims: The prevalence rates from the census were contrasted with those from the register along with variations in prevalence across the 26 counties of Ireland. Methods: 2011 and 2016 Census of Population prevalence per 1000 for children (aged 5–19 years) and adults (20 years and over) stratified by the 26 countries were contrasted with similar prevalence in the national register. Publically available data from the 2011 census in Northern Ireland and Scotland were obtained. Results: The Irish census identified nearly twice as many children and adults than were on the national register. Prevalence rates also varied across the 26 counties; more so on the register than the census. The Irish census had lower prevalence rates than Northern Ireland but higher than Scotland. Conclusions: Determining the prevalence of intellectual disability is challenging due to variations in terminology. A national register has advantages over reliance on census data for service planning.